A pulsed NMR relaxation and diffusion study of water in treated and untreated waterlogged wood - Bannister, David A. (1990)
Freezing curve, NMR relaxation data, and steady field gradient and pulsed field gradient experiments were conducted on samples of water-logged woods excavated from the Tudor warship, the Mary Rose and on similar samples impregnated with Polyethylene-Glycol solutions: the polymer used as a bulking agent to prevent decay.